Dynamic analysis and control for an electric vehicle with harpoon-shift synchronizer. (March 2019) - Mo, Wenwei; Walker, Paul D.; Zhang, Nong
Highlights: A dynamic model of powertrain system integrating the model of Harpoon-shift synchronizer for electric vehicles is built to investigate the gearshift dynamics. Harpoon-shift can improve gearbox efficiency, simplify gearshift control and improve shifting quality. Harpoon-Shift overcomes several shortcomings of the traditional synchronizers such as friction loss and wear. The optimized spring stiffness of Harpoon-Shift can reduce the shifting jerk significantly. Impacts of inertia and speed difference on the Harpoon-shift engaging performance are analyzed. Abstract: In order to improve shifting quality and the overall efficiency of electric vehicles, this paper presents a multi-gear electric vehicle powertrain system with a Harpoon-shift synchronizer as an alternative to the traditional cone clutch synchronizer. An original dynamic model of the powertrain integrating the model of the Harpoon-shift mechanism is established to investigate the transient responses of driveline system during gear shifting process. In addition, a shifting control method based on a special step function is proposed to improve the driving comfort. Upshift and downshift simulation results validate the effectiveness of the proposed mathematic model and control strategy. Then the torque spring stiffness of Harpoon-shift for each gear is optimized to reduce the shifting jerk. Furthermore, the influences of rotating inertia and speed difference on the shifting jerk of vehicle are quantitatively analyzed. Simulation results demonstrate that the jerk reduces considerably during engagement using the optimized torque springs, which shows the significant advantages of the proposed Harpoon-shift synchronizer compared to traditional synchronizers.